A CORPUS ASSISTED CRITICAL DISCOURSE ANALYSIS: REPRESENTATION OF #METOO MOVEMENT IN THE NEW YORK TIMES 2017-2023 - Eliza, Aulia Noor; Mumtaz, Rafida; Artha, Almira Fidela; Al Fajri, Muchamad Sholakhuddin (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to analyze The New York Times’s role in representing the #MeToo movement from 2017 to 2023. The study employs a descriptive qualitative approach with a Corpus-Based Critical Discourse Analysis (CBCDA) framework using Fairclough’s (2013) theory. The data were collected from 108 The New York Times articles containing the keyword “#MeToo” and compiled into a corpus using AntConc 3.4.4w. The analysis involved interpreting verbs and adjectives of collocation and concordance, followed by discourse practice and socio-cultural practice analysis. The findings reveal that the collocation of “#MeToo” is associated with verbs and adjectives that carry both positive and negative connotations. At the discourse practice level, The New York Times tends to portray women in the context of power inequality. Furthermore, the socio-cultural practice analysis indicates that the #MeToo movement reflects broader economic, political, and cultural dimensions. Overall, the results show that The New York Times embeds its ideology in representing the #MeToo movement. In conclusion, the study demonstrates that The New York Times not only reports on the #MeToo movement but actively participates in shaping its public meaning.